Changes in daily extreme temperature and precipitation events in mainland China from 1960 to 2016 under global warming. (20th October 2020) - Wang, Xuyang; Li, Yuqiang; Wang, Mingming; Li, Yulin; Gong, Xiangwen; Chen, Yinping; Chen, Yun; Cao, Wenjie
Abstract: Extreme climatic events have become a global concern. Understanding changes in these events is essential to support efforts to reduce their impacts. We investigated the spatial and temporal variation of 15 temperature and 11 precipitation extremal indices based on daily observations from 1960 to 2016 at 794 meteorological stations in mainland China. The regionally averaged temperature index trends were consistent with global warming. An abrupt change in the trends for warmth‐related indices mainly occurred from 1990 to 2000, and the year with an abrupt change for cold‐related indices appeared earlier (mainly around 1990). The numbers of warm days, warm nights, summer days, and tropical nights increased significantly. In contrast, the numbers of cool days, cool nights, ice days, and frost days decreased significantly. The coldest night temperature had a strong and significant warming trend (0.4°C·decade −1 ), whereas the number of frost days showed the fastest decrease (2.6 days·decade −1 ). The warmth and extremal indices decreased significantly with increasing latitude, whereas warming trends increased significantly with increasing longitude, and the warmth indices and extremal daily indices decreased with increasing elevation. The number of consecutive wet days decreased fastest, at 0.09 days·decade −1, and the daily intensity index increased fastest, at 0.09 mm·day −1 per decade. The extreme precipitation events decreased significantly with increasing latitude, but increased with increasing longitude. Large‐scale atmospheric circulation indices (the Arctic Oscillation and the Western Pacific Subtropical High Intensity and Area indices) and the Western Ridge Point strongly influenced the warm and cold extremes and contributed significantly to climate change in mainland China. The Western Ridge Point and Subtropical High Area were the dominant drivers of extreme temperature and precipitation events, respectively, in mainland China. Abstract : The numbers of warm days, warm nights, summer days, and tropical nights increased significantly. In contrast, the numbers of cool days, cool nights, ice days, and frost days decreased significantly. Large‐scale atmospheric circulation indices, such as the Arctic Oscillation, Western Pacific Subtropical High Intensity and Area indices, and the Western Ridge Point, strongly influenced the warm and cold extremes and contributed significantly to climate change in mainland China.